Juridical Review of Rejection of Applications for Adoption of Children - Muhammad Hamam Firdaus; Marisa Kurnianingsih (Proceeding International Conference Restructuring and Transforming Law, 2023)
The research aims to examine the problem regarding the rejection of the application for adoption by examining the judge's considerations in decision Number 0001/Pdt.P/2016/PA.Sbs, Number 404/Pdt.P/2017/Po and find out the legal consequences regarding the rejection of the application for adoption or adoption. child in the decision. This research method uses a normative juridical method, with a statutory approach and a case approach. The results of this research can be explained in the application for the adoption of a child, there are several applications that were rejected by the panel of judges as found in decision Number 0001/Pdt.P/2016/PA.Sbs, Number 404/Pdt.P/2017/Po which was due to the purpose of the adoption The child is proposed by the applicants and the conditions proposed in the adoption of the child are not relevant to the law in force in Indonesia and the legal consequence of refusing to adopt the child is that there is no transfer of responsibility to the child by the prospective adoptive parents, but the child is returned to the responsibility of the child. his biological parents due to the rejection of his application for adoption.